Transformation toward an eco-city: lessons from three Asian cities. (1st June 2016) - Hu, Mei-Chih; Wadin, Jessica Lagerstedt; Lo, Hsien-Chen; Huang, Jian-Yuan
Abstract: This comparative case study of three Asian cities (Penghu in Taiwan, Seoul in South Korea and Tianjin in China) elucidates the effects of different national approaches to eco-city development and the antecedents of the building of an eco-city. To better understand the Asian context, the three Asian cities of interest were compared with two European cities – Freiburg (Germany) and Samsö (Denmark). The effects of the approach to the development of an eco-city and the fitting of its business activities to the local context are investigated. The analysis identifies four transforming antecedents of the development of an eco-city in Asia, which are (1) utilization of a national approach and policy, (2) the presence of a dedicated local public authority, (3) the continuous engagement of local citizens, and (4) an infusion of national capability and business activity. The transformational development of an eco-city in Asia seeks to create a new techno-social regime that is based on sustainable solutions, whereas their respective national capabilities must be emphasized with an eye to efficiency, economy, and effectiveness simultaneously.